An automatic personalized internal fixation plate modeling framework for minimally invasive long bone fracture surgery based on pre-registration with maximum common subgraph strategy. (February 2019) - Liu, Bin; Liu, Wenpeng; Zhang, Song; Wang, Mingzhe; Yang, Yiqian; Zhang, Xiaohui; Qi, Wen; Qu, Xiaofeng
Abstract: In this paper, a visualization and modeling method for the internal fixation plate in personalized and minimally invasive long bone fracture surgery is presented. This framework mainly includes six sub-steps: firstly, the Principal Component Analysis (PCA) method is used to extract the 3D axis of the broken bone; secondly, the Gauss mapping method is utilized to segment the end surfaces of the broken bone; thirdly, the maximum common subgraph strategy is utilized to complete the end surface matching; fourthly, the OBB (Oriented Bounding Box) method is utilized to accomplish the pre-registration of the fracture surface; fifthly, the ICP (Iterative Closest Point) algorithm is utilized to achieve the fracture surface models' accurate alignment; lastly, the personalized bent internal fixation plate model can be reconstructed based on anchor points. Via this method, doctors can obtain the accurate and personalized internal fixation plate model that has the best matching geometric form to the patient's broken bones. This method can provide a well technique base and computational solution for the minimally invasive long bone fracture surgery. Highlights: We can obtain the accurate and personalized internal fixation plate model. The model can well match with the patient's broken bones. Maximum common subgraph strategy is utilized for the end surface matching. We can obtain a practical means for minimally invasive long bone fracture surgery.